Synthesis and Biological Activity of Some Aminobenzylated Mannich Bases of Benzaldehyde - CHALUVARAJU, K.C.; ISHWARBHAT, K. (Asian Journal of Chemistry, 2010)
Various aminobenzylated mannich bases of benzaldehyde were prepared through Mannich reaction by reacting it with secondary amines and amides. The structures of all the synthesized compounds have been confirmed on the basis of their IR, 1H NMR data and also screened for antibacterial activity.